THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION IN IMPROVING SORGHUM FARMING PERFORMANCE IN LAMONGAN DISTRICT - Aisyah Setiyaningasih; Rachmat Pambudy; Burhanuddin Burhanuddin (Jurnal Agribisnis Indonesia, 2026)
Sorghum (Sorghum bicolor (L.) Moench) is a promising commodity that is gaining popularity in Indonesia due to its broad adaptability. Entrepreneurial orientation encourages farmers to manage their agriculture professionally, profitably, and improve their economic resilience. Optimal farm performance has a direct impact on farmers' welfare, local food security, and the regional economy. This study aims to analyze the influence of internal and environmental factors on entrepreneurial orientation and sorghum farm performance in Lamongan Regency. The research method employed was Partial Least Squares Structural Equation Modeling (PLS-SEM), utilizing an embedded two-stage approach. Data were collected from 105 sorghum farmers through Likert scale questionnaires, interviews, and observations. The majority of sorghum farmers in Lamongan Regency were aged 42-57 years, at 48.57 percent, and were dominated by men at 84.76 percent. The education level was dominated by senior high school or equivalent at 80.95 percent. The experience of sorghum farming is still relatively new, namely 1-7 years, at 52.38 percent. The land area of the majority of sorghum farmers ranged from 200 to 2,299 m², at 77.14 percent. Land ownership amounted to 65.71 percent. Marketing of production was mostly through collectors at 84.76 percent. Farmers who are members of farmer groups amounted to 80.95 percent. The results showed that internal factors had a positive and significant effect on entrepreneurial orientation, with a coefficient of 0.532, and on the performance of sorghum farming in Lamongan Regency, with a coefficient of 0.326. Environmental factors also have a positive and significant effect on entrepreneurial orientation, with a coefficient of 0.306, and on the performance of sorghum farms in Lamongan Regency, with a coefficient of 0.340. Entrepreneurial orientation contributes positively and significantly to improving the performance of sorghum farming in Lamongan Regency with a coefficient of 0.284. All hypotheses can be accepted.